Evaluation of primary anastomosis in prepared/unprepared colo-rectal surgeries, and correlation with physiological and operative severity score for the enumeration of mortality and morbidity scoring - Bajaj, Jitin; Thakur, Dileep S.; Sharma, Deepti B.; Sharma, Dhananjaya (International Surgery Journal, 2016)
Background:Mechanical bowel preparation (MBP) is a common practice for colo-rectal surgeries. Our aim was to study whether preoperative MBP has a positive impact on the outcome of colo-rectal anastomosis, and their correlation with co-morbid conditions (calculated by POSSUM score). Methods: This was a prospective study. Patients for colo-rectal anastomosis were randomized into group A (MBP group), and group B (NMBP group). Record was made of demography, diagnosis, POSSUM score, and complications in the form of wound infection, anastomotic leak, intra-abdominal abscesses, reoperation and mortality. According to the POSSUM score, patients were divided into two groups, and complications were correlated according to it. Results:Neither of the primary outcome (leak, abdominal abscess, or wound infection), and secondary outcomes (reoperation and mortality) showed any difference. Similar were the results for physiological and operative severity score for the enumeration of mortality and morbidity (POSSUM) scoring. Conclusions:Mechanical bowel preparation and POSSUM predicted morbidity has no effect over integrity of the anastomosis, wound infection and abdominal abscesses in colo-rectal surgeries.